2022
DOI: 10.3390/ma15020608
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Thermoelectric Generator Based on Polycrystalline SiGe Thin Films

Abstract: Flexible and reliable thermoelectric generators (TEGs) will be essential for future energy harvesting sensors. In this study, we synthesized p- and n-type SiGe layers on a high heat-resistant polyimide film using metal-induced layer exchange (LE) and demonstrated TEG operation. Despite the low process temperature (<500 °C), the polycrystalline SiGe layers showed high power factors of 560 µW m−1 K−2 for p-type Si0.4Ge0.6 and 390 µW m−1 K−2 for n-type Si0.85Ge0.15, owing to self-organized doping in LE. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…We also should note that the maximum PF value at RT for the n-type Ge 1−x−y Si x Sn y layer is much higher than that of ntype polycrystalline Si 0.85 Ge 0.15 layers (0.15−3.9 μW cm −1 K −2 , dopant: Zn) 43,44) and n-type polycrystalline Ge layers (9.2 μW cm −1 K −2 , dopant: Sb) 37) grown on insulating surfaces by using ultra-low thermal budget processes due to better mobility which reflects high crystallinity; however, it is smaller than n-type epitaxial Ge layers on Si(001) (∼47 μW cm −1 K −2 , dopant: P) 38) and n-type polycrystalline Ge layers on insulator (∼23 μW cm −1 K −2 , dopant: P) 45) grown by using relatively high thermal budget dopant activation processes (around 500 °C) with MBE and solid-phase crystallization, respectively, due to degradation of the mobility by the Si 1−x Ge x alloy scattering. 46) In addition, we note that the PF obtained in the present study is smaller than that for the n-type polycrystalline Ge 1−x−y Si x Sn y layers mentioned in the introduction part (91 μW cm −1 K −2 ), 24) which may reflect the presence of the precipitates and difference in the elemental contents (Ge-rich or Si-rich).…”
Section: Resultsmentioning
confidence: 93%
“…We also should note that the maximum PF value at RT for the n-type Ge 1−x−y Si x Sn y layer is much higher than that of ntype polycrystalline Si 0.85 Ge 0.15 layers (0.15−3.9 μW cm −1 K −2 , dopant: Zn) 43,44) and n-type polycrystalline Ge layers (9.2 μW cm −1 K −2 , dopant: Sb) 37) grown on insulating surfaces by using ultra-low thermal budget processes due to better mobility which reflects high crystallinity; however, it is smaller than n-type epitaxial Ge layers on Si(001) (∼47 μW cm −1 K −2 , dopant: P) 38) and n-type polycrystalline Ge layers on insulator (∼23 μW cm −1 K −2 , dopant: P) 45) grown by using relatively high thermal budget dopant activation processes (around 500 °C) with MBE and solid-phase crystallization, respectively, due to degradation of the mobility by the Si 1−x Ge x alloy scattering. 46) In addition, we note that the PF obtained in the present study is smaller than that for the n-type polycrystalline Ge 1−x−y Si x Sn y layers mentioned in the introduction part (91 μW cm −1 K −2 ), 24) which may reflect the presence of the precipitates and difference in the elemental contents (Ge-rich or Si-rich).…”
Section: Resultsmentioning
confidence: 93%
“…The SiGe layers fabricated on a plastic substrate under the same conditions exhibit PF values of 560 µW m −1 K −2 for p‐type and 390 µW m −1 K −2 for n‐type. [ 124 ] The TEG sample with the plastic substrate maintained flexibility after the device fabrication process at 500 °C. The cross‐sectional power density is 2.6 mW cm −2 and the planer power density is 0.45 µW cm −2 (Figure 12b), which are not inferior to those of the sample with a glass substrate.…”
Section: Challenges Of Layer Exchangementioning
confidence: 99%
“…It is reported that to achieve maximum figure-of-merit, the optimal carrier concentration of the materials should be 10 18 -10 21 cm -3 , which falls under the category of heavily doped semiconductors [11,12]. As Seebeck coefficient and thermal conductivity are temperature-dependent parameters, different materials have performance peaks at optimal temperature window, e.g., Bi-Te-based materials show ZT of 0.8-1.1 around 200°C [13,14], Pb-Te-based alloys realize ZT of 1.2 between 200-600°C [15][16][17][18][19][20] and Si-Ge based alloys reach ZT of 0.5-0.9 above 600°C [21][22][23]. Other intermetallic alloys, such as skutterudites, clathrates, and Heusler alloys, are also reported to show ZT values up to 1 [24,25].…”
Section: Introductionmentioning
confidence: 99%